UPAYA PENINGKATAN KOMPTENSI GURU DALAM MENYUSUN RPP BERDIFERENSIASI MELALUI SUPERVISI KELOMPOK DENGAN PENGGUNAAN PENDEKATAN DIRECT - Subari Subari (Jurnal Ilmiah Global Education, 2023)
The title of this research is Efforts to Increase Teacher Competence in Compiling Differentiated Lesson Plans through Group Supervision Using a Direct Approach. The research method used is quantitative and qualitative with the implementation of school actions. Group supervision using a scientifically proven direct approach can increase teacher competence in preparing Differentiated Lesson Plans at SMAN 2 Madapangga, Bima Regency. This is evidenced by the increase in the number of teachers' lesson plans with good quality differentiation from 70% to 86% after group supervision using a direct approach. In addition, the number of Differentiated RPP also increased from 30% to 100%. The steps that lead to an increase in teacher competency in preparing the Differentiated RPP include the following steps: 1) Announcement of teacher supervision plans. 2) Implementation of group supervision, where each teacher group representative is asked to present their Differentiated RPP at a teacher meeting, then the principal and senior teacher provide input on the advantages and disadvantages of the teacher's Differentiated RPP. 3) Dividing teachers into several groups where each group is guided by a senior teacher. Finally, it was suggested to friends of madrasah/school heads, the implementation of group supervision with a direct approach is very suitable for increasing teacher competence in preparing Differentiated Lesson Plans, which so far is still an administration that is still difficult to obtain original from our teachers.